0173 Radiation-induced peritoneal mesothelioma after external beam radiotherapy for prostate adenocarcinoma: a longitudinal analysis of seer registries. (21st August 2017) - Farioli, Andrea; Zanardi, Francesca; Rizzello, Emanuele; Spatari, Giovanna; Morganti, Alessio Giuseppe; Violante, Francesco Saverio
Abstract : Objective: To investigate the association between external beam radiotherapy (EBRT) for prostate adenocarcinoma (PA) and malignant peritoneal mesothelioma (MPM) using data from the US Surveillance, Epidemiology and End Results (SEER) program. Methods: We identified PA cases diagnosed in 1973–2013 among patients aged ≥45 years. The follow-up started one year after the primary diagnosis (to exclude synchronous cancers and limit surveillance bias) and ended at the diagnosis of MPM, other malignancies, death, or at the study end (12/31/2013). We estimated hazard ratios (HR) and 95% confidence intervals (95% CI) of MPM for EBRT, compared to no radiotherapy, by fitting Cox models incorporating inverse probability weights to account for age at diagnosis, race, year of diagnosis, primary cancer surgery, SEER register, and county's mesothelioma relative risk (proxy for individual asbestos exposure). Results: We observed 34 MPM cases occurring in 4, 755, 045 person-years (rate of 0.7 per 1 00 000 person-years, 95% CI 0.5–1.0). The risk of MPM was higher among EBRT patients (HR 2.1, 95% CI 0.9–4.8) and increased steadily with increasing latency period (1–4 years, HR 1.3, 95% CI 0.4–4.6; 5–9 years, HR 1.9, 95% CI 0.5–7.7;≥10 years, HR 4.9, 95% CI 0.9–28). However, only 8 MPM were observed for latency periods≥10 years. Conclusions: Our study supports the hypothesis that EBRT for PA is associated with MPM. However, the incidence of MPM in our study population was very low; future studies should focus on high-risk populations (e.g. former asbestos workers) to evaluate the clinical significance of the observed association.